Suicide in services for mental health and substance use: A national hybrid registry surveillance system - Myhre, Martin Ø; Kildahl, Anine T; Astrup, Helene; Bergsager, Dagfinn; Walby, Fredrik A (Health informatics journal, 2023)
Suicide is strongly associated with mental health and substance use disorders, which makes mental health- and substance misuse services important areas for suicide prevention. The aim of The Norwegian Surveillance System for Suicide in Mental Health and Substance Use Services is to describe all suicide deaths in Norway that occur within one year after contact with mental health and substance misuse services. The study uses a hybrid registry case series design. It consists of a yearly linkage between the Norwegian Cause of Death Registry and the Norwegian Patient Registry, which is linked with a questionnaire. The linkage is conducted by using a cryptographic hash function of the deceased’s personal id, thus ensuring that the project can link data across sources without the use of directly identifiable information. This indirect linkage ensures the deceased’s confidentiality. Moreover, the The Norwegian Surveillance System for Suicide shows how administratively collected data can be harnessed and used for surveillance. Both use of hybrid registry designs and linkage through cryptographic hash functions might contribute to the development of health informatics as well as quality improvement in health care.